Stigma Perceived by Women Following Surgery for Breast Cancer - Tripathi, Lopamudra; Datta, Soumitra Shankar; Agrawal, Sanjit Kumar; Chatterjee, Sanjoy; Ahmed, Rosina (Indian Journal of Medical and Paediatric Oncology, 2017)
Context: Women undergoing treatment for breast cancer often have psychological morbidity and body image difficulties. The risk factors for increased levels of stigma in women with breast cancer have not been adequately studied. Aims: This study aimed at investigating the associations of high levels of stigma in women with breast cancer. Settings and Design: This cross-sectional study was conducted in a comprehensive cancer center in India and recruited women (n = 134) undergoing surgical treatment for breast cancer. Methods: Body image difficulties, including stigma and affective symptoms, were quantified, alongside disease- and treatment-related variables using standardized questionnaires. Statistical Analysis Used: Univariate analysis followed by multivariate logistic regression was performed to find the risk factors of high levels of stigma related to body image. Results: In the univariate analysis, high levels of stigma were associated with lesser educational attainment (odds ratio [OR] =2.92, confidence interval [CI] 1.25–6.8, P = 0.01), breast conservation surgery (BCS) as opposed to mastectomy (OR = 4.78, CI 2.07–11.03, P < 0.001), having an anxiety disorder (OR = 2.4, CI 1.09–5.33, P = 0.03), and depression (OR = 3.08, CI 1.37–6.89, P < 0.01). On multivariate logistic regression, with stigma as the dependent variable, being less educated (adjusted OR [AOR] 3.08, CI 1.18–8.04, P = 0.02) and opting for BCS (AOR 6.12, CI 2.41–15.5, P < 0.001) were associated with higher stigma. Conclusions: Women with breast cancer should be screened for distress and stigma. Women opting for BCS may still have unmet emotional needs on completion of surgery and should have access to psychological interventions to address stigma, affective symptoms, and body image problems.
Keywords: Body image; breast cancer; cancer; depression; oncology; stigma